Implementation and control of a new quadratic boost converter - Lim, Yan Zuo (Nanyang Technological University, 2023)
This report presents the design, implementation, and control of the New Quadratic Boost Converter, which is an extension to the traditional DC-DC boost converter and Quadratic Boost Converter.